Relationship between time under tension of muscle in resistance training with angiogenesis effective factors in inactive girls - Raziyeh Shiri; Mahsa Abdi; Sadegh Amani Shalamzari (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: One of the changes that occurs in the vascular structure of skeletal muscle during exercise to resolving stress is the process of angiogenesis that has been considered by researchers. Thus, the aim of this study was to investigate the effect of 6-week resistance training with different Time under Tension (TUT) on some serum vascular growth factors in inactive girls.Methods: 20 female volunteer students (mean age 22.3 yrs) were randomly and equally divided into two groups with different TUT of (1s – 1s) and (2s – 4s). Resistance training was performed for 6-week, three times per week, in eight stations,three sets, the intensity of 75% 1RM (10 repetitions) and 50% 1RM (5 repetitions) to equalize the training load in two groups. Blood samples were taken from the subjects before the training period and 48 hours after the last training session to evaluate the variables of VEGF, GH and endostatin. Data were analyzed by analysis of covariance.Results: There were no significant differences in serum levels of VEGF (P = 0.59) and GH (P = 0.89) between groups following six weeks of resistance training. But there were significant differences in serum endostatin level (P = 0.04) and leg strength (P = 0.01) between the two groups. Conclusion: Although there was no significant difference in angiogenesis related-factors between the two groups during six weeks and it is likely to need more time, but in the case of angiogenesis inhibitor, this difference was significant. Also, the more eccentric component was more associated with more strength in the 2s – 4s training.